A Dynamic Simulator for Slurry‐Phase Catalytic Olefin Copolymerization in a Series of CSTRs: Prediction of Distributed Molecular and Rheological Properties. Issue 4 (28th May 2018) - Pladis, Prokopios; Baltsas, Apostolos; Meimaroglou, Dimitrios; Kiparissides, Costas
Abstract: A comprehensive mathematical model is developed to simulate the dynamic Ziegler–Natta ethylene‐α‐olefins copolymerization in a series of slurry‐phase continuous stirred tank reactors. A generalized multisite kinetic mechanism is considered to describe the molecular and compositional developments (joint molecular weight‐copolymer composition distribution) in a series of continuous stirred tank reactors (CSTRs). Dynamic macroscopic mole balances are derived to calculate the dynamic evolution of all species concentrations in three phases (i.e., gas, liquid, and polymer) of the multiphase system. The polymer molecular properties (i.e., molecular weight distribution, short chain branching distribution, etc.) are determined by two different approaches, namely, the method of double moments and a Monte Carlo algorithm. Detailed thermodynamic calculations are carried out to calculate the solubility of all species in the various phases. Particular emphasis is given to the calculation of mass transfer rates from the gas to the continuous liquid phase and from the liquid to the polymer swollen phase. Comparison of model predictions with experimental measurements has shown that the present plant simulator is capable of simulating the dynamic operation of ethylene with α‐olefins copolymerization over a broad range of operating conditions and, thus, can be used in future process and product optimization and control of lab‐, pilot‐, and industrial‐scale plants. Abstract : A comprehensive mathematical simulator is presented for the dynamic operation of Ziegler–Natta ethylene‐α‐olefins copolymerization in a series of slurry‐phase continuous stirred tank reactors. Dynamic macroscopic mole balances are derived to calculate the dynamic evolution of all species concentrations in three phases (i.e., gas, liquid, and polymer) of the multiphase system.